Synergistic flame retardant and flame-retardant PS composite material and preparation method thereof

CN123003775APending Publication Date: 2026-10-30HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510548696.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]尽管PS复合材料的综合性能非常优异,但是PS复合材料易燃且燃烧速度快,燃烧时会产生淌滴和大量黑烟,在一些特定的应用领域中,比如通讯散热零部件材料,对PS复合材料阻燃性能要求很高,这限制了PS复合材料在这些特定领域中的应用

Benefits of technology

1.本发明制备的协效阻燃剂是聚苯乙烯包覆的氧化亚铁,加入到PS复合材料中,外层包覆的聚苯乙烯能够提高氧化亚铁与PS复合材料的相容性,有利于协效阻燃剂在PS复合材料中的分散;同时氧化亚铁会促进PS复合材料形成更加致密紧凑的炭层,减少PS复合材料内外的传热和传质,增强PS复合材料的吸热能力,并催化一氧化碳等不饱和气体的氧化,有效的抑制烟雾的生成,从而提升PS复合材料的阻燃性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to a kind of synergistic flame retardant and flame retardant PS composite material and its preparation method, the preparation method of the synergistic flame retardant includes the following steps: after mixing ferrous oxide, initiator, styrene, anhydrous ethanol, deionized water, heating reaction, filtration, washing, drying, obtain polystyrene coated ferrous oxide, it is synergistic flame retardant.The synergistic flame retardant prepared in the application is polystyrene coated ferrous oxide, added to PS composite material, the outer coating polystyrene can improve the compatibility of ferrous oxide and PS composite material, beneficial to the dispersion of synergistic flame retardant in PS composite material;While ferrous oxide will promote PS composite material to form more dense compact carbon layer, reduce the heat and mass transfer inside and outside PS composite material, enhance the endothermic capacity of PS composite material, and catalyze the oxidation of unsaturated gas such as carbon monoxide, effectively inhibit the generation of smoke, so as to improve the flame retardant performance of PS composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, and in particular to a synergistic flame retardant and a flame-retardant PS composite material and its preparation method. Background Technology

[0002] Polystyrene (PS) resin is a widely used high-molecular-weight polyester resin. PS composites have advantages such as good fatigue resistance, good heat resistance, and excellent dimensional stability. PS composites are lightweight, non-toxic, odorless, chemically stable, insoluble in common solvents at room temperature, and have low water absorption.

[0003] Although PS composites possess excellent overall performance, they are flammable and burn rapidly, producing dripping and large amounts of black smoke during combustion. In certain applications, such as heat dissipation components for communications, high flame retardancy is required for PS composites, limiting their use in these areas. Therefore, improving the flame retardancy and smoke suppression properties of PS composites is essential. Summary of the Invention

[0004] Based on this, the purpose of this invention is to provide a synergistic flame retardant and a flame-retardant PS composite material and a method for preparing the same. The synergistic flame retardant of this invention is polystyrene-coated ferrous oxide, which, when added to the PS composite material, can improve the flame-retardant properties of the PS composite material.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The present invention first provides a method for preparing a synergistic flame retardant, which includes the following steps: mixing ferrous oxide, initiator, styrene, anhydrous ethanol and deionized water and heating to react, filtering, washing and drying to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant.

[0006] The synergistic flame retardant prepared in this invention is polystyrene-coated ferrous oxide. When added to PS composite materials, the outer polystyrene coating improves the compatibility between ferrous oxide and PS composite materials, which is beneficial for the dispersion of the synergistic flame retardant in PS composite materials. At the same time, ferrous oxide promotes the formation of a denser and more compact char layer in PS composite materials, reduces heat and mass transfer between the inside and outside of PS composite materials, enhances the heat absorption capacity of PS composite materials, and catalyzes the oxidation of unsaturated gases such as carbon monoxide, effectively inhibiting the generation of smoke, thereby improving the flame retardant performance of PS composite materials.

[0007] As a further improvement to the above-mentioned solution of the present invention, the mass ratio of the ferrous oxide, the initiator, the styrene, the anhydrous ethanol, and the deionized water is (30-32):(0.1-0.3):(12-16):(60-80):(70-80). And / or, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide; And / or, the heating reaction is carried out at a temperature of 90-100°C for 7-9 hours; and / or, the drying is carried out at 80-90°C for 6-10 hours.

[0008] As a further improvement to the above-described solution of the present invention, the method for preparing ferrous oxide includes the following steps: S1. Mix ferric nitrate, sodium thiosulfate (or potassium thiosulfate), anhydrous ethanol, and deionized water, heat to react, and cool to room temperature to obtain solution A. S2. Mix the solution A, ammonia (or sodium hydroxide or potassium hydroxide), anhydrous ethanol, and deionized water, heat to react, and cool to room temperature to obtain solution B; filter, wash, and dry the solution B to obtain solid C; potassium thiosulfate can be used instead of ammonia. S3. Calcine the solid C to obtain ferrous oxide; the preparation equation for ferrous oxide is as follows: 2Fe 3+ +S2O3 2- +H₂O→2Fe 2+ +2SO4 2- +4H + Fe 2+ +OH - →Fe(OH)2 Fe(OH)2→FeO+H2O.

[0009] As a further improvement to the above-mentioned solution of the present invention, in step S1, the mass ratio of the ferric nitrate, the sodium thiosulfate, the anhydrous ethanol, and the deionized water is (30-40):(0.4-0.6):(50-60):(70-90). And / or, in step S1, the heating reaction is carried out at a temperature of 60-90°C for a time of 12-16 hours.

[0010] As a further improvement to the above-mentioned solution of the present invention, in step S2, the mass ratio of solution A, ammonia water, anhydrous ethanol and deionized water is (30-36):(8-12):(60-70):(100-120). And / or, in step S2, the heating reaction is carried out at a temperature of 80-90°C for a time of 8-16 hours; And / or, in step S2, the drying is performed at 60-80°C for 6-10 hours.

[0011] As a further improvement to the above-mentioned solution of the present invention, in step S3, the calcination is carried out under an inert atmosphere at 700-800°C for 10-12 hours.

[0012] The present invention also provides a flame-retardant PS composite material, which is prepared from the following components in parts by weight: 95-105 parts of PS, 18-20 parts of 2-carboxyethylphenyl hypophosphite, 3-5 parts of the synergistic flame retardant as described in any one of claims 1-6, and 0.1-0.5 parts of antioxidant.

[0013] As a further improvement to the above-mentioned scheme of the present invention, the antioxidant is at least one of tris(2,4-di-tert-butyl)phosphite (abbreviated as Irganox168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (abbreviated as Irganox1010), and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxyphenylmethyl)benzene (abbreviated as Irganox1330).

[0014] The present invention also provides a method for preparing the flame-retardant PS composite material as described above, which includes the following steps: mixing PS, 2-carboxyethylphenylphosphine, synergistic flame retardant and antioxidant in proportion, and then adding the mixture to a twin-screw extruder for extrusion granulation to obtain the flame-retardant PS composite material.

[0015] As a further improvement to the above-mentioned solution of the present invention, the twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 160-180℃, zone 2 temperature 210-250℃, zone 3 temperature 210-250℃, zone 4 temperature 210-250℃, zone 5 temperature 210-250℃, zone 6 temperature 210-250℃, die head temperature 210-250℃, and screw speed 200-280 r / min.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The synergistic flame retardant prepared in this invention is polystyrene-coated ferrous oxide. When added to PS composite material, the outer polystyrene coating improves the compatibility between ferrous oxide and PS composite material, which is beneficial to the dispersion of the synergistic flame retardant in PS composite material. At the same time, ferrous oxide promotes the formation of a denser and more compact carbon layer in PS composite material, reduces heat and mass transfer inside and outside PS composite material, enhances the heat absorption capacity of PS composite material, and catalyzes the oxidation of unsaturated gases such as carbon monoxide, effectively inhibiting the generation of smoke, thereby improving the flame retardant performance of PS composite material.

[0017] 2. The flame-retardant PS composite material of the present invention contains 2-carboxyethylphenylphosphine. The phosphorus element in 2-carboxyethylphenylphosphine can promote the dehydration and carbonization of the PS composite material during combustion, increase the residual carbon rate of the PS composite material, and thus enhance the flame-retardant performance of the PS composite material.

[0018] 3. The flame-retardant PS composite material of the present invention has excellent flame-retardant properties. Such a material has not been reported to date, and it has very important practical significance for expanding the application of PS composite materials. Detailed Implementation

[0019] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0021] The raw material information used in the following examples and comparative examples is as follows: PS (Model SKH-127): Manufactured by SK in South Korea; Ferric nitrate: Produced by Shandong Wenhui Chemical Co., Ltd. Sodium thiosulfate: Produced by Jinan Dewen Chemical Co., Ltd. Ammonia water: Produced by Jinan Junfeng Chemical Co., Ltd. Deionized water: Produced by Xiamen Aoquan Environmental Protection Technology Co., Ltd. Anhydrous ethanol: Produced by Shanghai Fangye Chemical Co., Ltd. Azobisisobutyronitrile (AIBN): Produced by Jinan Weizhen Chemical Co., Ltd. Styrene: Produced by Jinan Jiangtai Chemical Co., Ltd. Antioxidants: Irganox 168, Irganox 1010, Irganox 1330, manufactured by BASF; Commercially available ferrous oxide: produced by Jinan Huijinchuan Chemical Co., Ltd. 2-Carboxyethylphenylphosphonic acid, produced by Hubei Xinghengye Technology Co., Ltd.

[0022] The above-mentioned raw materials are only for illustrating the source and composition of the reagents used in the experiments of this invention, so as to fully disclose them, and do not imply that the invention cannot be achieved by using other similar reagents or reagents provided by other suppliers.

[0023] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.

[0024] Preparation Example 1 This preparation example prepares a synergistic flame retardant M1, and the preparation method includes the following steps: S1. Weigh 300g of ferric nitrate, 4g of sodium thiosulfate, 500g of anhydrous ethanol and 700g of deionized water and add them to a reactor vessel to mix. Then react at 60℃ for 12h and cool to room temperature to obtain solution A.

[0025] S2. Weigh 300g of solution A obtained in step S1, 80g of ammonia water, 600g of anhydrous ethanol, and 1.0kg of deionized water and add them to a reactor vessel to mix. Then react at 80℃ for 8h, cool to room temperature to obtain solution B, filter and wash solution B, and dry at 60℃ for 6h to obtain solid C.

[0026] S3. Place the solid C obtained in step S2 in a crucible under nitrogen atmosphere and calcine it at 700℃ for 10 h to obtain ferrous oxide.

[0027] S4. Weigh 300g of ferrous oxide obtained in step S3, 1g of azobisisobutyronitrile, 120g of styrene, 600g of anhydrous ethanol, and 700g of deionized water and add them to a reactor vessel. React at 90℃ for 7h, then filter, wash, and dry at 80℃ for 6h to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant M1.

[0028] Example 1 This embodiment provides a flame-retardant PS composite material P1, the preparation method of which includes the following steps: weighing 95 parts of PS, 18 parts of 2-carboxyethylphenylphosphine, 3 parts of synergistic flame retardant M1, and 0.1 parts of Irganox1010, mixing and stirring evenly to obtain a mixture; adding the mixture to a twin-screw extruder for extrusion granulation to obtain the flame-retardant PS composite material P1.

[0029] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 160℃, zone 2 temperature 210℃, zone 3 temperature 210℃, zone 4 temperature 210℃, zone 5 temperature 210℃, zone 6 temperature 210℃, die head temperature 210℃, and screw speed 200r / min.

[0030] Preparation Example 2 This preparation example prepares a synergistic flame retardant M2, and the preparation method includes the following steps: S1. Weigh 400g of ferric nitrate, 6g of sodium thiosulfate, 600g of anhydrous ethanol and 900g of deionized water and add them to a reactor vessel to mix. Then react at 90℃ for 15h and cool to room temperature to obtain solution A.

[0031] S2. Weigh 360g of solution A obtained in step S1, 120g of ammonia water, 700g of anhydrous ethanol, and 1.2kg of deionized water and add them to a reactor vessel to mix. Then react at 90℃ for 16h, cool to room temperature to obtain solution B, filter and wash solution B, and dry at 80℃ for 10h to obtain solid C.

[0032] S3. Place the solid C obtained in step S2 in a crucible under nitrogen atmosphere and calcine it at 800℃ for 12 hours to obtain ferrous oxide.

[0033] S4. Weigh 320g of ferrous oxide obtained in step S3, 3g of azobisisobutyronitrile, 160g of styrene, 800g of anhydrous ethanol, and 800g of deionized water and add them to a reactor vessel. React at 100℃ for 9h, then filter, wash, and dry at 90℃ for 10h to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant M2.

[0034] Example 2 This embodiment provides a flame-retardant PS composite material P2, the preparation method of which includes the following steps: weighing 105 parts of PS, 20 parts of 2-carboxyethylphenylphosphine, 5 parts of synergistic flame retardant M2, 0.1 parts of Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1330, mixing and stirring evenly to obtain a mixture; adding the mixture to a twin-screw extruder for extrusion granulation to obtain the flame-retardant PS composite material P2.

[0035] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 180℃, zone 2 temperature 250℃, zone 3 temperature 250℃, zone 4 temperature 250℃, zone 5 temperature 250℃, zone 6 temperature 250℃, die head temperature 250℃, and screw speed 280r / min.

[0036] Preparation Example 3 This preparation example prepares a synergistic flame retardant M3, and the preparation method includes the following steps: S1. Weigh 350g of ferric nitrate, 5g of sodium thiosulfate, 550g of anhydrous ethanol and 800g of deionized water and add them to a reactor vessel to mix. Then react at 75℃ for 14h and cool to room temperature to obtain solution A.

[0037] S2. Weigh 330g of solution A obtained in step S1, 120g of ammonia water, 700g of anhydrous ethanol, and 1.2kg of deionized water and add them to a reactor vessel to mix. Then react at 90℃ for 16h, cool to room temperature to obtain solution B, filter and wash solution B, and dry at 80℃ for 10h to obtain solid C.

[0038] S3. The solid C obtained in step S2 is placed in a crucible under nitrogen atmosphere and calcined at 750°C for 11 hours to obtain ferrous oxide.

[0039] S4. Weigh 310g of ferrous oxide obtained in step S3, 2g of azobisisobutyronitrile, 140g of styrene, 700g of anhydrous ethanol, and 750g of deionized water and add them to a reactor vessel. React at 95℃ for 8 hours, then filter, wash, and dry at 85℃ for 8 hours to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant M3.

[0040] Example 3 This embodiment provides a flame-retardant PS composite material P3, the preparation method of which includes the following steps: weighing 100 parts of PS, 19 parts of 2-carboxyethylphenylphosphine, 4 parts of synergistic flame retardant M3, 0.1 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1010, mixing and stirring evenly to obtain a mixture; adding the mixture to a twin-screw extruder for extrusion granulation to obtain the flame-retardant PS composite material P3.

[0041] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 170℃, zone 2 temperature 230℃, zone 3 temperature 230℃, zone 4 temperature 230℃, zone 5 temperature 230℃, zone 6 temperature 230℃, die head temperature 230℃, and screw speed 240r / min.

[0042] Preparation Example 4 This preparation example prepares a synergistic flame retardant M4, and the preparation method includes the following steps: S1. Weigh 335g of ferric nitrate, 5.8g of sodium thiosulfate (reducing agent), 553g of anhydrous ethanol, and 765g of deionized water and add them to a reactor vessel. Mix the mixture and react it at 78°C for 15 hours. Cool it to room temperature to obtain solution A.

[0043] S2. Weigh 326g of solution A obtained in step S1, 108g of ammonia water, 636g of anhydrous ethanol, and 1.05kg of deionized water and add them to a reactor vessel to mix. Then react at 88℃ for 13h, cool to room temperature to obtain solution B, filter and wash solution B, and dry at 68℃ for 9h to obtain solid C.

[0044] S3. Place the solid C obtained in step S2 in a crucible under nitrogen atmosphere and calcine it at 760°C for 11.5 h to obtain ferrous oxide.

[0045] S4. Weigh 319g of ferrous oxide obtained in step S3, 2.8g of initiator azobisisobutyronitrile, 135g of styrene, 668g of anhydrous ethanol, and 745g of deionized water and add them to a reactor vessel. Then react at 98℃ for 8.5h, filter, wash, and dry at 88℃ for 9.5h to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant M4.

[0046] Example 4 This embodiment provides a flame-retardant PS composite material P4, the preparation method of which includes the following steps: weighing 98 parts of PS, 18.5 parts of 2-carboxyethylphenylphosphine, 3.5 parts of synergistic flame retardant M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1330, mixing and stirring evenly to obtain a mixture; adding the mixture to a twin-screw extruder for extrusion granulation to obtain the flame-retardant PS composite material P4.

[0047] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 165℃, zone 2 temperature 215℃, zone 3 temperature 215℃, zone 4 temperature 215℃, zone 5 temperature 215℃, zone 6 temperature 215℃, die head temperature 215℃, and screw speed 205r / min.

[0048] Preparation Example 5 This preparation example prepares a synergistic flame retardant M5, and the preparation method includes the following steps: S1. Weigh 388g of ferric nitrate, 4.9g of sodium thiosulfate (reducing agent), 578g of anhydrous ethanol, and 838g of deionized water and add them to a reactor vessel to mix. Then react at 88℃ for 14.5h and cool to room temperature to obtain solution A.

[0049] S2. Weigh 328g of solution A obtained in step S1, 111g of ammonia water, 685g of anhydrous ethanol, and 1.18kg of deionized water and add them to a reactor vessel to mix. Then react at 88℃ for 15.2h, cool to room temperature to obtain solution B, filter and wash solution B, and dry at 78℃ for 9.8h to obtain solid C.

[0050] S3. The solid C obtained in step S2 is placed in a crucible under nitrogen atmosphere and calcined at 745°C for 11.8 h to obtain ferrous oxide.

[0051] S4. Weigh 318g of ferrous oxide obtained in step S3, 2.8g of initiator azobisisobutyronitrile, 155g of styrene, 735g of anhydrous ethanol, and 758g of deionized water and add them to a reactor vessel to mix. Then react at 93℃ for 8.8h, filter, wash, and dry at 86℃ for 8.8h to obtain polystyrene-coated ferrous oxide, which is the synergistic flame retardant M5.

[0052] Example 5 This embodiment provides a flame-retardant PS composite material P5, the preparation method of which includes the following steps: weighing 95 parts of PS, 19.5 parts of 2-carboxyethylphenylphosphine, 4.5 parts of synergistic flame retardant M5, 0.1 parts of antioxidant Irganox1010, and 0.1 parts of antioxidant Irganox168, mixing and stirring evenly to obtain a mixture; extruding the mixture from a twin-screw extruder to granulate, thereby obtaining the flame-retardant PS composite material P5.

[0053] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 175℃, zone 2 temperature 225℃, zone 3 temperature 225℃, zone 4 temperature 225℃, zone 5 temperature 225℃, zone 6 temperature 225℃, die head temperature 225℃, and screw speed 245r / min.

[0054] Comparative Example 1 This comparative example provides a PS composite material D1, the preparation method of which includes the following steps: weighing 95 parts of PS, 19.5 parts of 2-carboxyethylphenylphosphine, 4.5 parts of commercially available ferrous oxide, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mixing and stirring evenly to obtain a mixture; adding the mixture to a twin-screw extruder for extrusion granulation to obtain the PS composite material D1.

[0055] The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 175℃, zone 2 temperature 225℃, zone 3 temperature 225℃, zone 4 temperature 225℃, zone 5 temperature 225℃, zone 6 temperature 225℃, die head temperature 225℃, and screw speed 245r / min.

[0056] Test case The flame retardant properties of the PS composite materials of Examples 1-5 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0057] Table 1 Flame retardant performance test results

[0058] As can be seen from the results in Table 1, the flame retardant properties of the PS composite materials in Examples 1-5 are all better than those of the PS composite material in Comparative Example 1, which indicates that the PS composite material prepared by the present invention has better flame retardant properties.

[0059] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing a synergistic flame retardant, characterized in that, It includes the following steps: Ferrous oxide, initiator, styrene, anhydrous ethanol, and deionized water are mixed and heated to react. After filtration, washing, and drying, polystyrene-coated ferrous oxide is obtained, which is the synergistic flame retardant.

2. The method for preparing the synergistic flame retardant according to claim 1, characterized in that, The mass ratio of the ferrous oxide, the initiator, the styrene, the anhydrous ethanol, and the deionized water is (30-32):(0.1-0.3):(12-16):(60-80):(70-80). And / or, the initiator is at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide; And / or, the heating reaction is carried out at a temperature of 90-100°C for 7-9 hours; and / or, the drying is carried out at 80-90°C for 6-10 hours.

3. The method for preparing the synergistic flame retardant according to claim 1, characterized in that, The method for preparing the ferrous oxide includes the following steps: S1. Mix ferric nitrate, sodium thiosulfate, anhydrous ethanol, and deionized water, heat to react, and cool to room temperature to obtain solution A; S2. Mix the solution A, ammonia, anhydrous ethanol, and deionized water, heat to react, and cool to room temperature to obtain solution B; filter, wash, and dry the solution B to obtain solid C; S3. Calcining the solid C yields ferrous oxide.

4. The method for preparing the synergistic flame retardant according to claim 3, characterized in that, In step S1, the mass ratio of the ferric nitrate, the sodium thiosulfate, the anhydrous ethanol, and the deionized water is (30-40):(0.4-0.6):(50-60):(70-90). And / or, in step S1, the heating reaction is carried out at a temperature of 60-90°C for a time of 12-16 hours.

5. The method for preparing the synergistic flame retardant according to claim 3, characterized in that, In step S2, the mass ratio of solution A, ammonia, anhydrous ethanol, and deionized water is (30-36):(8-12):(60-70):(100-120). And / or, in step S2, the heating reaction is carried out at a temperature of 80-90°C for a time of 8-16 hours; And / or, in step S2, the drying is performed at 60-80°C for 6-10 hours.

6. The method for preparing the synergistic flame retardant according to claim 3, characterized in that, In step S3, the calcination is carried out under an inert atmosphere at 700-800°C for 10-12 hours.

7. A flame-retardant PS composite material, characterized in that, It is prepared from the following components in parts by weight: 95-105 parts of PS, 18-20 parts of 2-carboxyethylphenyl hypophosphite, 3-5 parts of the synergistic flame retardant as described in any one of claims 1-6, and 0.1-0.5 parts of antioxidant.

8. The flame-retardant PS composite material according to claim 7, characterized in that, The antioxidant is at least one of tris(2,4-di-tert-butyl)phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxyphenyl)benzene.

9. A method for preparing a flame-retardant PS composite material as described in any one of claims 7-8, characterized in that, It includes the following steps: PS, 2-carboxyethylphenylphosphine, synergistic flame retardant, and antioxidant are mixed in a certain proportion and then added to a twin-screw extruder for extrusion granulation to obtain flame-retardant PS composite material.

10. The method for preparing flame-retardant PS composite material according to claim 9, characterized in that, The twin-screw extruder includes six temperature zones arranged in sequence: zone 1 temperature 160-180℃, zone 2 temperature 210-250℃, zone 3 temperature 210-250℃, zone 4 temperature 210-250℃, zone 5 temperature 210-250℃, zone 6 temperature 210-250℃, die head temperature 210-250℃, and screw speed 200-280 r / min.